Dislipidemia e índice de masa corporal elevado como factores de riesgo para hiperplasia benigna de próstata - Simón Cruz, David (2020)
Introduction: Benign prostatic hyperplasia (BPH) is the most frequent urological disease in men. Despite its generalized prevalence, the etiology is not well understood. Obesity is involved in BPH due to its relationship with metabolic and endocrine changes. There is little information on the role of lipids in prostate growth so there is a need for further research in this area. Objective: To determine if dyslipidemia and high body mass index are risk factors for the development of benign prostatic hyperplasia. Material and Method: An observational, case and control study was conducted. A population of 299 patients  40 years was taken into account, of which 159 patients were randomly selected and divided into 53 for the cases and 106 for the controls. Results: It was found that there was no association between high BMI and BPH (χ²: 0.347, OR: 0.813, IC: 0.409 – 1.617, p  0.555). There was no association between dyslipidemia and BPH ((χ²: 3.389, OR: 2.22, IC: 0.937 – 5.261, p  0.066). There was no association between CT, TG, LDL and HDL independently with BPH. Conclusion: The BMI  25 kg/m2 is not a risk factor to develop HBP, in the same way neither the dyslipidemia nor any of its components are risk factors for HBP.